Impact of molecular weight on the mechanism of cellular uptake of polyethylene glycols (PEGs) with particular reference to P-glycoprotein - Tingting Wang; Yingjie Guo; Yang He; Tianming Ren; Lei Yin; John Paul Fawcett; Jingkai Gu; Huimin Sun (Elsevier, 2020)
Polyethylene glycols (PEGs) in general use are polydisperse molecules with molecular weight (MW) distributed around an average value applied in their designation e.g., PEG 4000. Previous research has shown that PEGs can act as P-glycoprotein (P-gp) inhibitors with the potential to affect the absorption and efflux of concomitantly administered drugs. However, questions related to the mechanism of cellular uptake of PEGs and the exact role played by P-gp has not been addressed. In this study, we examined the mechanism of uptake of PEGs by MDCK-mock cells, in particular, the effect of MW and interaction with P-gp by MDCK-hMDR1 and A549 cells. The results show that: (a) the uptake of PEGs by MDCK-hMDR1 cells is enhanced by P-gp inhibitors; (b) PEGs stimulate P-gp ATPase activity but to a much lesser extent than verapamil; and (c) uptake of PEGs of low MW (<2000 Da) occurs by passive diffusion whereas uptake of PEGs of high MW (>5000 Da) occurs by a combination of passive diffusion and caveolae-mediated endocytosis. These findings suggest that PEGs can engage in P-gp-based drug interactions which we believe should be taken into account when using PEGs as excipients and in PEGylated drugs and drug delivery systems.